Taxing households energy consumption in the EU: The tax burden and its redistributive effect - Antonio F. Amores; Sofía Maier; Mattia Ricci (European Commission, Joint Research Centre (JRC), 2022)
The taxation of energy consumption is a central topic in the current policy debate of the European Union. While raising energy taxation is part of the European Commission's strategy for achieving its 2030/50 climate targets, the ongoing dramatic increases in the price of energy products are raising calls for reducing their taxation. Therefore, a close consideration of the incidence and redistributive effects of energy taxation is crucial to design compensatory measures and to ensure support for the Green transition. In this paper, we employ the EUROMOD microsimulation model to estimate the burden and the redistributive impact of energy consumption taxation on households across Member States. In doing so, we break down the role played by differences in consumption patterns, rates of taxation and their regressivity. We find that countries where energy taxation is the highest are often not the ones where its incidence on household income is the strongest. At the same time, the highest inequality impact is not always taking place in countries with the most regressive energy taxation. We therefore stress the importance of considering, not only the level of energy consumption taxation, but also its regressivity and its incidence over household income when assessing its inequality cost.
Keywords: 330; Energiekonsum; Energiesteuer; Privater Haushalt; Steuerbelastung; Verteilungswirkung; EU-Staaten